Evaluating the use of a novel low-cost measurement insole to characterise plantar foot strain during gait loading regimes - Crossland, Sarah R.; Siddle, Heidi J.; Brockett, Claire L.; Culmer, Peter (Frontiers in Bioengineering and Biotechnology, 2023)
Under plantar loading regimes, it is accepted that both pressure and shear strain biomechanically contribute to formation and deterioration of diabetic foot ulceration (DFU).Plantar foot strain characteristics in the at-risk diabetic foot are little researched due to lack of measurement devices. Plantar pressure comparatively, is widely quantified and used in the characterisation of diabetic foot ulceration risk, with a range of clinically implemented pressure measurement devices on the market. With the development of novel strain quantification methods in its infancy, feasibility testing and validation of these measurement devices for use is required. Initial studies centre on normal walking speed, reflecting common activities of daily living, but evaluating response to differing gait loading regimes is needed to support the use of such technologies for potential clinical translation. This study evaluates the effects of speed and inclination on stance time, strain location and strain response using a low-cost novel strain measurement insole. The STrain Analysis and Mapping of the Plantar Aspect (STAMPS) insole has been developed, and feasibility tested under self-selected normal walking speeds to characterise plantar foot strain, with testing beyond this limited regime required. A treadmill was implemented to standardise speed and inclination for a range of daily plantar loading conditions. A small cohort, comprising of five non-diabetic participants, were examined at slow (0.75 m/s), normal (1.25 m/s) and brisk (2 m/s) walking speeds and normal speed at inclination (10% gradient). Plantar strain active regions were seen to increase with increasing speed across all participants. With inclination, it was seen that strain active regions reduce in the hindfoot and show a tendency to forefoot with discretionary changes to strain seen. Stance time decreases with increasing speed, as expected, with reduced stance time with inclination. Comparison of the strain response and stance time should be considered when evaluating foot biomechanics in diabetic populations to assess strain time interval effects. This study supports the evaluation of the STAMPS insole to successfully track strain changes under differing plantar loading conditions and warrants further investigation of healthy and diabetic cohorts to assess the implications for use as a risk assessment tool for DFU.